Optimizing intersectoral collaboration between health and education: the Health Bridges study. (2nd February 2017) - Burgess, T.; Braunack-Mayer, Annette; Tooher, R.; Collins, J.; O'Keefe, M.; Skinner, R.; Watson, M.; Ashmeade, H.; Proeve, C.; Marshall, H.
Abstract: Background: Schools are increasingly asked to participate in a range of public health programs, but there has been little consideration of the impact of these programs on policy and/or implementation. We investigated intersectoral collaboration between the health and education sectors using a case study of a school-based immunization program (SBIP). Methods: The study was undertaken in South Australia. We undertook an ethnographic review examining health and education system functioning at a variety of levels using a mixed methods approach, informed by an interactive and multidirectional knowledge transfer framework. Results: Facilitators for intersectoral collaboration included: explicit responsibilities for specific activities; clear communication channels; including the core values of each sector in planning and implementation; and collaborative development of health educational programs. Including consumers as key stakeholders in planning and implementing intersectoral programs is important. While the SBIP itself is currently successful, threats to its sustainability were identified. Conclusions: Outcomes included: (i) a clearer understanding of the functioning of the SBIP in SA including wide-ranging and practical recommendations to facilitate the implementation of the program in both sectors, including revisions to enhance the experience for students; (ii) a broader outcome focusing on identification of barriers and facilitators for intersectoral collaboration and suggestions for enhancing such collaborations.